(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the pedagogical opportunities of the value-based approach in mother tongue education from theoretical and methodological perspectives. Mother tongue education is interpreted as an important pedagogical means of fostering national and universal values among learners. The study highlights the essence, principles, and didactic potential of the value-based approach. Furthermore, it provides a scientific rationale for integrating values into the content of mother tongue education, identifies the pedagogical conditions conducive to developing learners’ value consciousness, value-based attitudes, and value-oriented behavior, and discusses contemporary methodological approaches that support this process. The article also explores the theoretical and practical possibilities of implementing the value-based approach in mother tongue education and substantiates its pedagogical significance in promoting learners’ moral and ethical development, communicative competence, and personal growth.